Evaluating the risk to humans from mineral oils in foods: Current state of the evidence. (February 2020) - Bevan, R.; Harrison, P.T.C.; Jeffery, B.; Mitchell, D.
Abstract: Key issues around the evaluation of risks to humans from mineral oils in food and feedstuffs are discussed. MOHs (MOAH and MOSH) occur in food due to intentional use, contamination from environmental sources and during transport/processing, or through migration from food contact materials. Problems in setting and enforcing human health guidelines for MOH include uncertainty around MOH toxicity and the specialist expertise needed for analysis of complex food matrices. Currently, the method of choice for measuring mineral oils is LC-GC-FID, however some complex food matrices also require additional analytical techniques to differentiate between some naturally occurring hydrocarbons and those from other sources, including of petrogenic origin. This requires the skills of an experienced analyst. Significant toxicological gaps for MOHs prevent robust human health risk assessment and the derivation of guidance values. As food-grade mineral oils are virtually MOAH-free, the key issue explored here is the relevance to humans of liver (micro)granulomas observed in F344 rats following oral intake. Available data suggest that despite the ubiquitous nature of MOH in the human diet, the prevalence of liver lipogranulomas in the population is low. These are not associated with inflammation and based on current evidence are not considered of human health significance. Highlights: MOHs are complex mixtures, historically characterised on physical properties, not chemical structures/molecular weight. The method of choice for the routine quantification of mineral oils, LC-GC-FID, is sometimes not sufficient for the characterisation of complex food matrices. Toxicological studies in F-344 and Sprague-Dawley rats show very different sensitivities to the adverse effects of MOSH. Differences in sensitivities between rat strains are likely due to variation in absorption and accumulation of MOSH. Characterisation of MOH used in early toxicity studies is often poor, impacting on their use for evaluating food safety.